Using Google Forms for Online Listening Test: Does It Work? - Kurniawati, Dewi; Lestari, Sri (English Education: Jurnal Tadris Bahasa Inggris, 2020)
The major objective of this study was to investigate the use of Google forms in giving listening comprehension test and to know the students’ responses toward online test by using Google forms. From this study, it is also hoped that it can provide information to English teachers or lecturers who teach listening subject about how to use Google form and how to upload an audio and video in this online platform. The methodological approach taken in this study was a descriptive qualitative method. Data for this study were collected using observation, students’ listening comprehension tests, and open-ended questionnaires. The participants of this study were 62 students in one English education program of one university in Bandar Lampung. In summary, the results in this study indicate that the students have positive responses toward the use of Google form in the listening comprehension test. It can be seen from their response and their answers to the questionnaire given, the result of observation of using Google forms, and the result of their listening comprehension test, the majority of the students got good scores. The average score of the test was 77,74. The median of the score was 80.   Key words: Google forms, assessment, Listening Comprehension, students’ response.